mTOR-Dependent Oxidative Stress Regulates oxLDL-Induced Trained Innate Immunity in Human Monocytes - Sohrabi, Yahya; Lagache, Sina M. M.; Schnack, Lucia; Godfrey, Rinesh; Kahles, Florian; Bruemmer, Dennis; Waltenberger, Johannes; Findeisen, Hannes M. (Frontiers in Immunology, 2019)
Introduction: Cells of the innate immune system particularly monocytes and macrophages have been recognized as pivotal players both during the initial insult as well as the chronic phase of atherosclerosis. Recently it has been shown that oxidized low-density lipoprotein (oxLDL) induces a long-term pro-inflammatory response in monocytes due to epigenetic and metabolic reprogramming, an emerging new concept called trained innate immunity. Changes in the cellular redox state are crucial events in the regulation of many physiologic functions in macrophages including transcription, differentiation and inflammatory response. Here we have analyzed the role of reactive oxygen species (ROS) in regulating this proinflammatory monocyte priming in response to oxLDL-treatment. Methods and results: Human monocytes were isolated and incubated with oxLDL for 24h. After 5 days resting time, oxLDL treated cells produced significantly more inflammatory cytokines upon restimulation with the TLR2-agonist Pam3cys. Furthermore, oxLDL incubation induced persistent mTOR activation, ROS formation, HIF1α accumulation and HIF1α target gene expression, while pharmacologic mTOR inhibition or siRNA mediated inhibition of the mTORC1 subunit Raptor prevented ROS formation and proinflammatory priming. mTOR dependent ROS formation was associated with increased expression of NAPDH oxidases and necessary for the emergence of the primed phenotype as antioxidant treatment blocked oxLDL priming. Inhibition of cytosolic ROS formation could also block mTOR activation and HIF1α accumulation suggesting a positive feedback loop between mTOR and cytosolic ROS. Although mitochondrial ROS scavenging did not block HIF1α-accumulation at an early time point (24h), it was persistently reduced at day 6. Therefore, mitochondrial ROS formation appears to occur initially downstream of the mTOR-cytoROS-HIF1α feedback loop but appears to be a crucial factor that controls the long-term activation of the mTOR-HIF1α-axis. Conclusion: In summary, our data demonstrate that mTOR dependent ROS production controls oxLDL-induced trained innate immunity phenotype in human monocyte derived macrophages. Pharmacologic modulation of these pathways might provide a potential approach to modulate inflammation, associated with aberrant monocyte activation, during atherosclerosis development.